Hyper JK-algebras - Mohammad Ali Hashemi (Journal of Hyperstructures)
In this paper, we introduce the notion of hyper JK-algebras and investigate these algebras properties. Moreover, we present relationships between hyper JK-algebras and pseudo hyper BCK-algebras and hyper pseudo MV-algebras under some conditions.